ANALISIS IKON BAHASA DALAM LOGO OBJEK PEMAJUAN KEBUDAYAAN KOTA BANDUNG - Matin, Sella Sabrina; Aji, Widianto Satrio; Nagara, Martien Roos (Jurusan Seni Rupa ISBI Bandung, 2024)
Language is one of the key aspects of human life that plays a vital role in communication and social interaction. An in-depth study of the structure and function of language is important for understanding the complex dynamics in society. This research aims to explore and analyze the Language Icons in the Logos of Bandung City Cultural Advancement Objects. This research adopts a qualitative descriptive method involving researchers who use themselves as the main tool to examine the condition of natural objects. Data collection involves triangulation, which is the integration of many methodologies. The Bandung College of Technology student team has collaborated with the Bandung City Culture and Tourism Office in designing 10+1 OPK logos and icons in accordance with Law No. 5 of 2017 concerning Cultural Advancement, as an effort to preserve and maintain Bandung city culture in accordance with city regional regulations Bandung Number 7 of 2023. It is hoped that the design of the OPK Logo and Icon will make it easier for the public to understand and study all forms of culture in the city of Bandung.